Lifetime physical inactivity is associated with lung cancer risk and mortality. (2018) - Cannioto, Rikki; Etter, John Lewis; LaMonte, Michael J.; Ray, Andrew D.; Joseph, Janine M.; Qassim, Emad Al; Eng, Kevin H.; Moysich, Kirsten B.
Abstract: Introduction: Investigations of the independent associations of physical inactivity with cancer endpoints have been mounting in the epidemiological literature, in part due to the high prevalence of physical inactivity among cancer patients and to evidence that inactivity associates with carcinogenesis via pathways independent of obesity. Yet, physical inactivity is not currently recognized as a well-established risk or prognostic factor for lung cancer. As such, we examined the associations of lifetime physical inactivity with lung cancer risk and mortality in a hospital-based, case-control study. Presentation of case: materials and methods: The analyses included data from 660 lung cancer patients and 1335 matched cancer-free controls. Multivariable logistic regression analyses were utilized to assess the association between lifetime physical inactivity and lung cancer risk, and Cox proportional hazards models were utilized to estimate the association between lifetime physical inactivity and mortality among lung cancer cases. Results: We observed a significant positive association between lifetime physical inactivity and lung cancer risk: [Odds ratio (OR)=2.23, 95% confidence interval (CI): 1.77–2.81]; the association remained significant among never smokers (OR=3.00, 95% CI:1.33-6.78) and non-smokers (OR=2.33, 95% CI: 1.79–3.02). We also observed a significant positive association between lifetime physical inactivity and lung cancer mortality [Hazard ratio (HR)=1.40, 95% CI: 1.14–1.71]; the association remained significant in non-smokers (HR=1.51, 95% CI: 1.16–1.96). Discussion/conclusion: These data add to the body of evidence suggesting that physical inactivity is an independent risk and prognostic factor for cancer. Additional research utilizing prospectively collected data is needed to substantiate the current findings.